Moralna wymowa gestu namaszczenia stóp i głowy Jezusa w Quaestio de Maria Magdalena et Maria sorore Lazari et Marthae Joachima z Fiore - Grzeszczak, Jan (Vox Patrum, 2018)
Joachim of Fiore (1135-1202) – a Middle Age exegete and mystic – is the author of an impressive work on the vision of history, whose most renown element is the tertius status, i.e. the age of the Holy Spirit which precedes the end of the world and the Final Judgment. As an author, Joachim was also interested in the history of religious life in the Middle Ages and in various exegetical tools which he developed to analyze this subject. In his works, especially the minor ones, he also discusses practical problems related to religious life in the 12th century. The small tractate, Questio de Maria Magdalena et Maria sorore Lazari et Marthae, has been preserved in a single 13th century manuscript and is kept in the Biblioteca Antoniana in Padua. In his exegesis on various Gospel passages which deal with the anointing of Jesus’ feet and head in Galilee and Bethany, Joachim of Fiore intends to show that the actions of women who performed this gesture possess a hidden moral significance: the certainty concerning the internal unity that occurs between contemplation and the virtue of humility. An example of this unity is Mary of Bethany who anointed the feet of Jesus and wiped them with her hair (cf. Jn 12:3) as a person who is humble and – at the same time – given to contemplation. Still – according to Joachim – as a righteous person, she had the right to reach for the head of the Savior.